PERBEDAAN BESARAN PENCAHAYAAN ALAMI PADA DUA MODEL BUKAAN JENDELA Studi Kasus: Ruang Dasen Jurusan Teknik Sipil dan Perencanaan FT UNY - Ikhwanuddin, Mahmud Rosyid (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2007)
AbstractA window in building could have double function. The One, it canpermit outdoor air to flow across rooms. The other,it can permit daylightor sun ray come into the room. The sum of illumination is determined bysome factors: form, size, position, and proportion between window androom. Overdose of daylight will make air hotter andgJare. While lowdaylight intention can make working not to pleasant. Thus, knowing whatis the good window shape is important.This research used quasi-experiment method. The location oneis in one room of among civil and planning department lecturer rooms.The object of research is the window of room, on the north side. Thewindow has been researched are the window with bouvenHcht and thewindow without bouvenlicht. The Window without bouvenlicht isconstructed of fixed glass. While, the window \Nith bouvenlichtis thesame as one and it is separated by walL The dependent variable arewide of window, intensity of sky illumination, the position of window andpoints of measurements. The windows width of two models are 27.225cm2 and 27.195 cm2. The sky illumination is 10.000 lux. The position ofwindow and the shape of room is fixed. The measurement wasconducted at 11.00 pm to 01.00 am, and it was used Luxmeter NT1332,the production of Sanwa Electric Inst:-ument co. ltd.The result of this research explain two thing. The first, there issignificant different in point 1 in al! line. The illumination of windowwithout bouvenlicht is higher than window with bouvenlicht. While inpoint 2 until 6, the illumination of windo'lv without bouvenlicht is lowerthan window with bouvenlicht. The second, comparing to illuminationstandard for activities, there is no significant different in all line, becausethe difference illumination is no more than 100 hundred lux, except atpoint 1 line C.Keywords: daylight, window shape. illumination